SYNTHESIS OF VOLTAGES OF UNIFORM PWM IN TIME REGULATION - A. G. Stryzhniou; A. N. Rusakovich; A. A. Shykhau (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article describes a process of synthesis and qualitative assessment of the harmonic composition of voltages of multiple and single PWM pulses in time regulation, being, along with amplitude, frequency and phase method, one of control methods of an asynchronous motor. The main point of time regulation is that a pause after any two single PWM pulses with different polarity or after any two groups of multiple PWM pulses with different polarity changes during a process of regulation. Feature of time regulation is that a motor has fast response in the range of small-signal of control and good linearity of speed-torque characteristics in the whole control range. Analytical expressions of parameters of PWM pulses ai and ti are obtained which allow to simplify considerably a process of formation and implementation of time regulation using tabular or indexed-tabular methods. These expressions allow not only to define voltage amplitude of  harmonic but also to perform qualitative assessment of harmonic composition of output voltages at time regulation. It is specified that harmonic frequencies wi = w0/q change in inverse proportion to magnitude of parameter q during a process of regulation and there is a replacement of a fundamental frequency by frequencies of higher harmonics.The offered approach allows to synthesize voltage of uniform single and multiple PWM pulses and to perform their comparative and qualitative analysis and the obtained expressions can be used at modeling of AC motor work. Voltage of multiple PWM pulses which is formed using stepped reference voltage with even quantity of steps in a half period and a pause on a zero level has the best parameters by criterion of a minimum of harmonic components and a maximum of a factor of anharmonicity Kнс at time regulation.